2011
DOI: 10.1007/s10815-011-9695-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated day 3 FSH/LH ratio: a marker to predict IVF outcome in young and older women

Abstract: Purpose To evaluate the value of elevated day 3 FSH/LH ratio in predicting IVF results in young and older women. Methods One hundred seventy-four women with normal day 3 FSH levels undergoing IVF treatment were studied. Patients were divided into two groups according to basal FSH/LH ratio: Group 1(FSH/LH ≥3, n043) and Group 2 (FSH/LH <3, n0131). The effects of FSH/LH ratio on IVF outcomes were compared. Also, the impact of elevated FSH/LH levels on younger (<35 years; n0113) and older (≥35 years; n061) women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
11
2
Order By: Relevance
“…It has previously been shown that FSH:LH ratio can be used as predictor of pregnancy outcome in infertile women [35], but this was not confirmed in the present study. It has also been demonstrated that AMH is a better marker than age, FSH on cycle day 3 or inhibin B for prediction of IVF pregnancy success [36], which could neither be shown in the present study.…”
Section: Discussioncontrasting
confidence: 93%
“…It has previously been shown that FSH:LH ratio can be used as predictor of pregnancy outcome in infertile women [35], but this was not confirmed in the present study. It has also been demonstrated that AMH is a better marker than age, FSH on cycle day 3 or inhibin B for prediction of IVF pregnancy success [36], which could neither be shown in the present study.…”
Section: Discussioncontrasting
confidence: 93%
“…Our results also showed a significant reduction in the number of embryos in group A who showed lower LH: FSH ratio, Seckin et al finding was near to our results, but he classified the patients according to their age as he found that women ≥35 years old with elevated FSH/LH ratio had significantly lower number of retrieved oocytes, lower transferred good grade embryos count, and lower pregnancy rate versus women at the same age but with lower FSH/LH ratio. [38]. Liu et al, and Rehman et al found an inverse relationship between FSH-LH ratio and the number of day 3 embryos, and number of blastocysts, while in our study the count of blastocysts were lower in patients with lower LH: FSH ratio but not significant [24,31].…”
Section: Discussion:-contrasting
confidence: 46%
“…FSH and LH levels are commonly used for the prediction of the ovarian reserve in the early follicular phase even though they have a lower predictive value. Recently, there was a report that elevated day 3 FSH/LH ratio ≥2 is associated with higher rates of cancellation in In Vitro Fertilization (IVF)-embryo transfer cycles ( 14 ) and some studies have shown that the day 3 FSH to LH or LH to FSH ratio can be used as a predictor of the ovarian reserve ( 14 , 15 , 16 , 17 , 18 , 19 ). The day 3 LH/FSH ratio is relatively easy to obtain and shows more predictive power as the day 3 FSH level alone.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that patients with polycystic ovaries have statistically significant higher LH levels and LH/FSH ratios than patients with normal ovaries ( 13 ). And some studies suggested that the LH/FSH ratio could be used as a marker of fertility or ovarian reserve ( 14 , 15 , 16 , 17 , 18 , 19 ). However, only serum FSH and AMH levels have been still focused and regarded as useful markers to predict the ovarian reserve in women of reproductive age.…”
Section: Introductionmentioning
confidence: 99%